Malignant perivascular epithelioid cell tumor (PEComa) of the uterus with late renal and pulmonary metastases: a case report with review of the literature - Parwani Anil V; Armah Henry B (BMC, 2007)
Abstract Background Perivascular epithelioid cell tumor (PEComa), other than angiomyolipoma (AML), clear cell sugar tumor (CCST), and lymphangioleiomyomatosis (LAM), is a very rare mesenchymal tumor with an unpredictable natural history. The uterus is the most prevalent reported site of involvement of PEComa-not otherwise specified (PEComa-NOS). To the best of our knowledge, about 100 PEComa-NOS have been reported in the English Language medical literature, of which 38 were uterine PEComa-NOS. These reported cases of uterine PEComa-NOS have usually shown clinically benign behavior, but 13 tumors, three of them associated with tuberous sclerosis complex (TSC), exhibited local aggressive behavior and four of them showed distant metastases. Case presentation We report the case of a 59-year-old woman, who presented with renal and pulmonary lesions seven years after the initial diagnosis of uterine leiomyosarcoma. Left nephrectomy and right middle lobe wedge resection were performed. Histological and immunohistochemical analysis of the renal and pulmonary lesions, in addition to retrospective re-evaluation of the previous uterine tumor, led to the final diagnosis of malignant uterine PEComa with late renal and pulmonary metastases. All three lesions had the typical histological appearance of PEComa-NOS showing a biphasic growth pattern with continuous transition between spindle cells and epithelioid cells, often arranged around vascular spaces. Immunohistochemically, the tumor cells of both phenotypes in all three lesions stained for melanocytic (HMB-45 and Melan-A/MART-1) and myoid (desmin, smooth muscle actin, and muscle-specific actin/all muscle actin/HHF-35) markers. Conclusion The findings indicate that despite the small number of reported cases, PEComas-NOS should be considered tumors of uncertain malignant potential, and metastases to other organs might become evident even several years after the primary diagnosis.